Characterization of spiral inductor topologies for GaAs MMIC applications - Bueta, Emmanuel S.
The aim of this project was to design on-chip spiral inductors to be used for low noise amplifiers MMIC. The inductors used Gallium Arsenide as its substrate prepared by the National Institute of Physics (NIP). Characterize on wafer inductors produced by the fabrication technology of the NIP as well as recommend how these inductors can be improved was investigated. In addition to this, spiral inductors that are suitable to their fabrication process were designed and examined. It was observed that the substrate thickness and the gold inductor trace affect the performance of the inductor. Common topologies such as the octagon, circle, rectangle, square and the hexagon spiral inductors were compared in terms of the inductance value, quality factor and self-resonant frequency. Likewise, the trends for the variation in the number of turns, spacing between metal traces, conductor width and the area occupied were also explored. Results show that the area occupied by the inductor greatly affects its inductance and self-resonant frequency. On the other hand, the octagon has the highest quality factor from all the topologies. Lastly, other topologies such as the inductor with decreasing inner trace width an the twin spiral were investigated. The technique of Bahl[1[ where the inner trace widths gradually decreases was verified. The Q factor of the DTW was greater compared to the base square spiral.